Inclusive leadership and employee innovative behavior: moderated by creative self-efficacy (Journal of Namibian Studies : History Politics Culture, 2023)
In the academic and other sectors, Employee Innovative Behavior (EIB) is a significant problem. Employees in the e-commerce sector are experiencing more job instability as a result of the growing uncertainty imposed by COVID-19. Career sustainability (CS) is now in concern. Creative self-efficacy (CSE) is a person's confidence in their capacity to create. CSE creative thinking and problem-solving, which may lead to professional success and innovation. Additionally, CS must be taken into account because one's perception of the sustainability of a career affects their propensity to innovate. Based on the theory of job demands and resources (JDR), this study uses a combination of theoretical construction and quantitative analysis to examine how creative self-efficacy influences the relationship between inclusive leadership and employee innovation behavior in China's e-commerce sector, particularly livestream e-commerce. Employee perceptions of occupational sustainability were examined for their potential mediating effects. This research examined the role of CSE as a mediator in the aforementioned connections as well as the effect of CS leadership, which is EIB, on inclusive leadership (IL). The construct validity and path connections are examined by structural equation modeling. The findings demonstrate that the risk created by the COVID-19 epidemic for China's live streaming e-commerce, IL can only assist the translation of employment assets into workplace EIB when employees perceive CS. The findings demonstrated that IL enhances EIB through CSE. The research provides a theoretical basis for IL and EIB and conceptually overcomes the gap. We guide companies and executives on how to actually give workers tools at work that will support their CS while advancing their EIB.